2019
DOI: 10.1021/acsomega.8b02628
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-Layered Rutile TiO2 Nanorods as Alternative Photoanode in Dye-Sensitized Solar Cells

Abstract: In this paper, dye-sensitized solar cell (DSSC) performance of the less explored polymorph of TiO 2 , rutile, has been explored, and its performance has been modified with polyaniline (PANI) wrapping on the surface. For this purpose, highly crystalline rutile nanorods have been synthesized without any growth-directing substrates, employing a hydrothermal treatment. Further, to understand the phase composition and morphology, the synthesized nanorods and PANI-layered nanorods have been ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Besides, Kretzschmar et al observed that the electron lifetime in photoanode films fabricated with NRs was 2 times longer compared to that with nanoparticles [21]. Apart from efficient electron transport, 1-D nanostructures with tunable lengths ranging from hundreds of nanometers to micrometers are also promising light-scattering centers with enhanced optical propagation distance within the films and improved light collection efficiencies [22,23,24]. Nevertheless, excessive loss of accessible surface area and thus insufficient dye loading of these ZnO nanostructures limits their attainable photovoltaic efficiency to a relatively low level, making them less competitive in current DSCs embodiments.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Kretzschmar et al observed that the electron lifetime in photoanode films fabricated with NRs was 2 times longer compared to that with nanoparticles [21]. Apart from efficient electron transport, 1-D nanostructures with tunable lengths ranging from hundreds of nanometers to micrometers are also promising light-scattering centers with enhanced optical propagation distance within the films and improved light collection efficiencies [22,23,24]. Nevertheless, excessive loss of accessible surface area and thus insufficient dye loading of these ZnO nanostructures limits their attainable photovoltaic efficiency to a relatively low level, making them less competitive in current DSCs embodiments.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the photovoltaic performance of the synthesized composite rods with the starting precursor TiO 2 and also a standard P25 TiO 2 sample, DSSC devices have been fabricated as per our previous methods. [ 11,27 ] The measured performance of the fabricated DSSC device is shown in Figure . The J–V characteristics of the DSSCs fabricated with synthesized CR, TP, and P25 are presented in Figure 7a.…”
Section: Resultsmentioning
confidence: 99%
“…[ 51,52 ] As evident from the microstructure analysis and the diffuse reflection spectra in Figure 6b, the slanting rods in the current case could favor adequate light scattering property and rapid electron transfer both could be responsible for the enhanced light harvesting to enhance the cell efficiency. [ 27,53,54 ] The particles, on the other hand, suffer from trapping/detrapping phenomenon in the conduction pathway between the grain boundaries, and therefore result in lesser efficiency than a rod. The enhanced photovoltaic performance of the composite may also arise from the band gap position of the mixture of phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations